2008
DOI: 10.1093/ndt/gfn604
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with chronic kidney disease in an adult population from southern China

Abstract: In the general adult population from southern China, 12.1% has either proteinuria, haematuria and/or reduced eGFR, indicating the presence of kidney damage, with an awareness of only 9.6%. The high prevalence and low awareness of CKD in this population suggest an urgent need for CKD prevention programmes in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
131
12
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 29 publications
17
131
12
4
Order By: Relevance
“…Almost one half of them had at least one of the three markers: 25% had only MAU and/or proteinuria but not diminished eGFR, while 21% had eGFR below 60 mL/min/1.73 m 2 -14% without MAU and proteinuria and 7% with MAU and/or proteinuria. These results cannot be compared with those obtained in several massive screenings carried out in the general population where the prevalence of GFR below 60 mL/min/1.73 m 2 was between 3.2 and 11.2% 2,11,17,26,27 and albuminuria between 2.4 and 15.6%. 2,11,[26][27][28][29] The almost twice as high prevalence of CKD markers found here, where three groups of patients at increased risk of CKD were involved, is comparable to values determined in studies that also targeted different at-risk populations.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Almost one half of them had at least one of the three markers: 25% had only MAU and/or proteinuria but not diminished eGFR, while 21% had eGFR below 60 mL/min/1.73 m 2 -14% without MAU and proteinuria and 7% with MAU and/or proteinuria. These results cannot be compared with those obtained in several massive screenings carried out in the general population where the prevalence of GFR below 60 mL/min/1.73 m 2 was between 3.2 and 11.2% 2,11,17,26,27 and albuminuria between 2.4 and 15.6%. 2,11,[26][27][28][29] The almost twice as high prevalence of CKD markers found here, where three groups of patients at increased risk of CKD were involved, is comparable to values determined in studies that also targeted different at-risk populations.…”
Section: Discussionmentioning
confidence: 59%
“…These results cannot be compared with those obtained in several massive screenings carried out in the general population where the prevalence of GFR below 60 mL/min/1.73 m 2 was between 3.2 and 11.2% 2,11,17,26,27 and albuminuria between 2.4 and 15.6%. 2,11,[26][27][28][29] The almost twice as high prevalence of CKD markers found here, where three groups of patients at increased risk of CKD were involved, is comparable to values determined in studies that also targeted different at-risk populations. The initial data of the well-known kidney early evaluation program (KEEP) that targeted persons with diabetes, hypertension, or a family history of diabetes or hypertension or CKD showed that, among 6071 participants, 29% had albuminuria and 16% had eGFR below 60 mL/min/1.73 m 2 .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The initial data of the The Kidney Early Evaluation Program (KEEP) program that targeted persons with diabetes, hypertension, or a family history of diabetes or hypertension or CKD showed that among 6,071 participants 29% had ≥A2 categoriy of albuminuria and 16% had eGFR below 60 mL/min/1.73 m 2 [18]. In the present study 15.1% of all patients had high albuminuria and 17.9% had eGFR below 60 mL/min/1.73 m 2 . Our previous study included 1617 patients with hypertension, diabetes and age over 60 years, who were unaware of earlier kidney disease.…”
Section: Discussionmentioning
confidence: 55%
“…In several mass screenings carried out in the general population the prevalence of eGFR below 60 ml/min/1.73m 2 was between 3.2% and 11.2% [12][13][14][15] and ≥A2 categoriy of albuminuria between 2.4% and 15.6% [12][13][14][15][16][17]. In screening studies that included subjects at risk for CKD even higher prevalence was reported.…”
Section: Discussionmentioning
confidence: 99%